Quercetin protects cadmium-induced renal injuries in mice by inhibiting cell pyroptosis - Wang, Juyu; Yang, Jieyan; Liu, Kai; Qu, Weijie; Wang, Kuan; Zhao, Yu; Zhou, Yaxiong; Liu, Xiang; Zhang, Limei; Gu, Xiaolong (Frontiers in Veterinary Science, 2023)
The toxic heavy metal cadmium (Cd) has a significant impact on kidney health. Documents manifested that non-toxic flavonoid quercetin can reduce Cd-induced kidney damage by reducing oxidative stress and inhibiting apoptosis, while the effect of quercetin on Cd-induced renal cell pyroptosis has not been elucidated. In this study, we established a model of Cd poisoning treated with quercetin both in vitro and in vivo.Results revealed that quercetin effectively reversed the decrease in Cd-induced cell viability. Furthermore, Cd increased blood urea nitrogen while reducing GPX and SOD levels, caused histopathological injuries in kidney with a significantly elevated cell pyroptosis characterized by enhanced levels of proteins representing assembly (NLRP3) and activation (pro IL-1β, cleaved IL-1β and IL-18) of NLRP3 inflammasome as well as pyroptosis executor (pro caspase-1, cleaved caspase-1). However, quercetin administration alleviated kidney injuries above by decreasing cell pyroptosis. Overall, it suggests that kidney cells are susceptible to pyroptotic cell death due to Cd exposure; while quercetin exhibits protective effects through cell pyroptosis inhibition.